2020
DOI: 10.9734/ajaees/2020/v38i1130457
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Livelihood Diversification of Rural Households in Sylhet

Abstract: Livelihood diversification is considered as a constructive way to improve the livelihood of poor people in rural Bangladesh. This study examines the level of livelihood diversification and the determinants of livelihood diversification of rural households in Sylhet division by using both primary and secondary data. The primary data were collected from two districts of Sylhet division by adopting simple random sampling procedures. A face to face interview was employed to collect cross section data of total 210 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…The results from the study pointed out that, for income generation, the respondents mostly adopted different livelihood activities. The findings support the report of Sharma et al [27], who reported that most households in India have two or even more livelihood options.…”
Section: Extent Of Livelihood Diversificationsupporting
confidence: 91%
“…The results from the study pointed out that, for income generation, the respondents mostly adopted different livelihood activities. The findings support the report of Sharma et al [27], who reported that most households in India have two or even more livelihood options.…”
Section: Extent Of Livelihood Diversificationsupporting
confidence: 91%
“…Tingkat diversifikasi sumber pendapatan rumah tangga di pedesaan Patanas Jawa Barat tergolong relatif tingggi tetapi tidak memiliki hubungan yang kuat dengan tingkat pendapatan dan pola diversifikasinya tidak begitu jelas. Tingkat diversifikasi pendapatan dalam penelitian ini diukur dengan Indeks Entropy yaitu indeks yang mengaitkan jumlah penyerapan tenaga kerja pada masing-masing sumber pendapatan [10]. Sumatera Barat sebagai salah satu provinsi di Indonesia dengan struktur ekonomi yang masih didominasi oleh sektor pertanian merupakan sebuah daerah yang cukup menarik untuk menjadi kajian kemiskinan sektor pertanian.…”
Section: Pendahuluanunclassified
“…This research is in line with [13] that by diversifying farmer household, they have the ability to cope with the impact of losses and accelerate recovery time when facing disasters. Diversification is risk minimization strategy that is effectively applied by rural farmer households to meet their needs [25].…”
Section: Livelihood Diversificationmentioning
confidence: 99%